2013
DOI: 10.1038/ncomms3427
|View full text |Cite
|
Sign up to set email alerts
|

Tumour angiogenesis regulation by the miR-200 family

Abstract: The miR-200 family is well known to inhibit the epithelial–mesenchymal transition, suggesting it may therapeutically inhibit metastatic biology. However, conflicting reports regarding the role of miR-200 in suppressing or promoting metastasis in different cancer types have left unanswered questions. Here we demonstrate a difference in clinical outcome based on miR-200's role in blocking tumour angiogenesis. We demonstrate that miR-200 inhibits angiogenesis through direct and indirect mechanisms by targeting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
309
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 364 publications
(323 citation statements)
references
References 40 publications
10
309
1
3
Order By: Relevance
“…We silenced miRs in ECs using miR inhibitors and RNAifect reagent (Qiagen) as described in the supplemental methods. VEGFR1 and VEGFR2 were silenced in RF24 cells and annexin A2 in HMVECs was silenced with either control or target siRNAs using Lipofectamine 2000 reagent (Invitrogen) as described previously (33). The expression of annexin A2, miRs, and tight junction proteins was determined using quantitative real-time PCR and Western blot analyses as described previously (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…We silenced miRs in ECs using miR inhibitors and RNAifect reagent (Qiagen) as described in the supplemental methods. VEGFR1 and VEGFR2 were silenced in RF24 cells and annexin A2 in HMVECs was silenced with either control or target siRNAs using Lipofectamine 2000 reagent (Invitrogen) as described previously (33). The expression of annexin A2, miRs, and tight junction proteins was determined using quantitative real-time PCR and Western blot analyses as described previously (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…Almog et al (2012Almog et al ( , 2013 emphasized the role of miR-NA-190 in the reversal of fast-growing angiogenic tumors toward prolonged tumor dormancy. Pecot et al (2013) and Li et al (2013) emphasized the critical role of miRNA-200 in regulating epithelial-to-mesenchymal transition, which are key processes in invasion, progression, and metastasis. Lim et al (2013), in a study of pleural effusion or ascites samples in stage IV breast cancer patients, added to these observations and demonstrated the involvement of the miRNA-200 family in the process of nonstem to a stem-like phenotypic conversion.…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, other mediators of angiogenesis (e.g., platelet-derived growth factor, fibroblast growth factor, the polycomb group protein enhance Zeste homolog 2 [EZH2], notch family, the angiopoietin [Ang]-TIE system, and the miR-200 family of miRNA) are likely to play a role. 37,38 There is a small but growing body of literature that initial tumor response to anti-angiogenic therapy may paradoxically be followed by enhanced tumor progression by promoting an invasive phenotype. Experimental models have recently shown that tumors can develop anti-VEGF escape programs associated with metastatic dissemination to lymph nodes and distant sites.…”
Section: Discussionmentioning
confidence: 99%